Towards equitable commissioning for our multiethnic society: a mixed-methods qualitative investigation of evidence utilisation by strategic commissioners and public health managers - S Salway; D Turner; G Mir; B Bostan; L Carter; J Skinner; K Gerrish; GTH Ellison (National Institute for Health Research, 2013)
Background: The health-care commissioning cycle is an increasingly powerful determinant of the health services on offer and the care that patients receive. This study focuses on the mobilisation and use of evidence relating to ethnic diversity and inequality. Objective: To describe the patterns and determinants of evidence use relating to ethnic diversity and inequality by managers within commissioning work and to identify promising routes for improvement. Methods: In-depth semistructured interviews with 19 national key informants and documentation of good practice across England. Detailed case studies of three primary care trusts involving 70+ interviews with key strategic and operational actors, extensive observational work and detailed analysis of related documentation. A suite of commissioning resources based on findings across all elements were tested and refined through three national workshops of key stakeholders. Results: Commissioners often lack clarity on how to access, appraise, weight or synthesise diverse sources of evidence and can limit the transformational shaping of services by a narrow conceptualisation of their role. Attention to evidence on ethnic diversity and inequality is frequently omitted at both national and local levels. Understanding of its importance is problematic and there are gaps in this evidence that create further barriers to its use within the commissioning cycle. Commissioning models provide no reward or sanction for inclusion or omission of evidence on ethnicity and commissioning teams or partners are not representative of minority ethnic populations. Neglect of this dimension within national drivers results in low demand for evidence. This organisational context can promote risk-averse attitudes that maintain the status quo. Pockets of good practice exist but they are largely dependent on individual expertise and commitment and are often not shared. Study findings suggested the need for action at three levels: creating an enabling environment; equipping health-care commissioners; and empowering wider stakeholders. Key enabling factors would be attention to ethnicity within policy drivers; senior-level commitment and resource; a diverse workforce; collaborative partnerships with relevant stakeholders; and the creation of local, regional and national infrastructure. Limitations: It was harder to identify enablers of effective use of evidence in this area than barriers. Including a case study of an organisation that had achieved greater mainstreaming of the ethnic diversity agenda might have added to our understanding of enabling factors. The study was conducted during a period of fundamental restructuring of NHS commissioning structures. This caused some difficulties in gathering data and it is possible that widespread change and uncertainty may have produced more negative narratives from participants than would otherwise have been the case. Conclusions: Knowledge mobilisation and utilisation within the commissioning cycle occurs in the context of dynamic interactions between individual agency, organisational context and the wider health-care setting, situated within the UK sociopolitical milieu. Our findings highlight isolated pockets of good practice amidst a general picture of limited organisational engagement, low priority and inadequate skills. Findings indicate the need for specific guidance alongside incentives and resources to support commissioning for a multiethnic population. A more comprehensive infrastructure and, most importantly, greater political will is needed to promote practice that focuses on reducing ethnic health inequalities at all stages of the commissioning cycle. Funding: The National Institute for Health Research Health Services and Delivery Research programme.